Water Treatment Installation Network Design In Kali Veda Housing - Merauke. Issue 1 (May 2021) - Paresa, J; Utary, C; Riadi, MS
Abstract: The rapid population growth that makes Merauke Regency need to be anticipated, especially in the amount of waste that can damage infrastructure such as roads, bridges, drainage, good health. To find out the dimensions of a wastewater installation by considering the capacity of the house needed from a house in the planning location. The research method used is the calculation, calculation and design According to the population to Obtain the population, the dimensions of construction of the WWTP and the design results According to the population. The results of the study of wastewater in the residential area of Kali Veda in Merauke vary greatly, ranging from floating in light gray, brown to black, starting from the smell of waste water (replace). The amount of wastewater is determined to be 60-80%. The value of community sanitation in the score is not good Because The ideal average value (Mi) is <37.25 with a value of 37.13%. Communal wastewater with a plan for 20 years. The population is 1, 875 people, the criteria is 80 L / person / day. The average discharge is 42 liters / day / person, peak discharge is 75.6 liters / day / person. Processing capacity of 142.8 m3 in 2037. The design of the fat separator volume is 29.54 m3, the reservoir Leveling / wastewater design has a volume of 47.27 m3, the initial settling tank has a volume of 29.54 m3, settling volume 29, 54 m. Filter media is used as a medium for the plastic material, durable, has a large specific area, light and Also has a large volume of the cavity so that the deadlock media is very small. The pipe diameter of (black water) is 100 mm, material from PVC, Pipe diameter (gray water) is 100 mm, material from PVC. The diameter of the main pipe is 150 mm.